2020
DOI: 10.3390/ma13071573
|View full text |Cite
|
Sign up to set email alerts
|

Q-Switch Nd:YAG Laser-Assisted Elimination of Multi-Species Biofilm on Titanium Surfaces

Abstract: (1) Background: The relatively high prevalence of peri-implantitis (PI) and the lack of a standard method for decontamination of the dental implant surface have pushed us to conduct further research in the field. Bacterial biofilms were found to play a primordial role in the etiology of PI. Therefore, the aim is to evaluate the efficacy of a laser-assisted elimination of biofilm protocol in the removal of a multi-species biofilm on titanium surfaces. (2) Methods: In total, 52 titanium discs (grade 4) were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 45 publications
(61 reference statements)
1
14
0
Order By: Relevance
“…A study showed that the Er,Cr:YSGG laser with 1 Watt of power, for 30 s, is capable of the complete elimination of A.baumannii and P.aeruginosa biofilm on the implant surface without damaging the surface topography [ 25 ]. Regarding the use of the other lasers, such as Nd:YAG, a recent study [ 26 ] showed that Q-Switch Nd:YAG laser-assisted biofilm removal has provided a significant elimination of the biofilm on titanium surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that the Er,Cr:YSGG laser with 1 Watt of power, for 30 s, is capable of the complete elimination of A.baumannii and P.aeruginosa biofilm on the implant surface without damaging the surface topography [ 25 ]. Regarding the use of the other lasers, such as Nd:YAG, a recent study [ 26 ] showed that Q-Switch Nd:YAG laser-assisted biofilm removal has provided a significant elimination of the biofilm on titanium surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…The irradiation parameters used in this study were similar to the irradiation parameters used by Namour et al [21,22] based on the theoretical modeling of the optimal energy density respecting the implant surfaces' porosity.…”
Section: Laser Protocol and Irradiation Parametersmentioning
confidence: 99%
“…This resulted in the total absence of carbon and without causing any morphological change of the irradiated implant surfaces. In a later study, Namour et al [22] demonstrated that similar irradiation protocol with the Q-switch Nd: YAG laser was able to significantly eliminate the multi-species biofilm from the titanium surface [22]. The authors did not assess the disinfection state of that irradiated titanium surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Decontaminating (or detoxifying) the oral biofilm-contaminated titanium surface without altering it is fundamental for the treatment of periimplantitis [ 35 ]. Laser treatment has been proved to be effective in the decontamination of oral biofilm-contaminated titanium surfaces [ 36 , 37 ]. Several types of lasers have been studied for this purpose.…”
Section: The Use Of Lasers In Clinical Dentistrymentioning
confidence: 99%